(untitled) (Proceedings OPTIMAL, 2025)
Introduction: Breast cancer often causes anxiety in patients undergoing chemotherapy due to its prolonged and repetitive process, characterized by mood swings, fatigue, sleep disturbances, and emotional instability. One effective non-pharmacological intervention to reduce anxiety is music therapy, which can help regulate emotions, provide relaxation, and address psychological issues. Purpose: This study analyzes the effect of classical music therapy onthe anxiety levels of breast cancer patients undergoing chemotherapy at RSUD Tugurejo. Method: The type of research used is a quantitative method with a pre- experimental design approach and the research design is a one group pre-post test design. The research instrument used was a questionnaire where the questionnaire was not tested for validity and reliability because these tests had already been carried out. The study population consisted of 48 patients with breast cancer. The analytical test used is the Wilxocon test. Result: The p value = 0.000 was obtained and a negative rank was obtained for 48 respondents, which means that Ho was rejected and Ha was accepted. This shows that there is an influence of classical music therapy on the anxiety level of breast cancer patients undergoing chemotherapy at Tugurejo Regional Hospital. Conclusion: There is an influence between classical music therapy on the anxiety level of breast cancer patients and chemotherapy at Tugurejo District Hospital, with the pre-post test score criteria showing a negative rank as many as 48 respondents experienced a decrease in anxiety, indicated by the p value = 0.000. Keywords : Music Therapy, Anxiety Levels, Breast Cancer, Chemotherapy.